Study of Chlorine Use in Water Treatment at the Giri Menang Regional Drinking Water - Azwaruddin, Azwaruddin; Abdullah, Taufik; Wahyuningsih, Sri (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Population growth causes the need for clean water to increase. Disinfectants that are often used in the water treatment process include Chlorine. The right Chlorine residue is one of the important aspects that ensures water reaches consumers with good quality. The purpose of this study is to conduct a study on the use of chlorine in raw water treatment at the Giri Menang Mataram regional drinking water company. This research is a study; this study was carried out in the working area of the Regional Drinking Water Company Giri Menang Mataram. This Research is a study on the suitability of chlorine levels in raw water at the Giri Menang Mataram Regional Drinking Water Company. The stages of the study begin with preparation, data collection, data analysis, discussion and producing study results to determine the suitability of chlorine levels with applicable regulations. From this research, the results obtained are that the manufacture of chlorine in the Giri Menang Mataram Regional Drinking Water Company is not in accordance with the calculation for chlorine needs in each water source, resulting in a lot of sediment. It is hoped that the Giri Menang Regional Drinking Water Company can review the use of chlorine in accordance with the appropriate dosage calculation.